APLIKASI PENGOLAHAN DATA INVENTARIS PADA PUSAT LABORATORIUM KOMPUTER (STUDI KASUS : STMIK-NH JAMBI): INVENTORY DATA PROCESSING APPLICATIONS, PHP, BOOTSTRAP, FRAMEWORK CODEIGNITER, UML, USE CASE, ACTIVITY DIAGRAM - Lisdarti (FORTECH (Journal of Information Technology), 2018)
In process inventory data processing, where research is done so with computerized standards. In the process of borrowing and returns of goods are still manually. The purpose of the practicum research report writing this is to create a web-based program specifically to facilitate logging inventory, borrowing and returns of goods using the programming language PHP, CodeIgniter framework Bootstrap, and MySQL as the database in the application inventory data processing goods at the Central computer lab STMIK Nurdin of Jambi Hamzah web based. The methodology used in the writing of the report job practice is field research, the study of the literature and research laboratories. The analysis phase consists of: UML (Unified Modeling Language), Use Case diagrams, Activity diagrams, and Class Diagrams in designing databases, data structures, design, specification of input and output processes and stages of implementation. The results of the analysis and design of data-processing application is expected to provide ease in the process of penginventarisan, so that it can save you time, effort and cost. Inconclusive data processing applications can help in the search of the data items, borrowing, payback, and the making of the report. For advice on this application can be developed by adding logic calculations and processes needed in the future.